Analysis of the causative factors of chronic energy deficiency and the health impact on adolescent girls - Delly Handayani; Retno Widowati; Vivi Silawati; Rukmaini (KHD-Production, 2026)
Chronic Energy Deficiency (CED) among adolescent girls remains a major public health concern. This condition affects not only physical health but also psychological well-being and overall quality of life, necessitating a comprehensive study of its contributing factors and impacts. This study aimed to identify the factors contributing to CED and assess its impact on the health of adolescent girls. A quantitative design with a descriptive correlational approach was employed. Using stratified random sampling by grade level, 184 respondents were selected using Slovin's formula. Data were collected via standardized questionnaires, Mid-Upper Arm Circumference (MUAC) measurements, and hemoglobin examinations. Data analysis used Pearson's Correlation and multiple linear regression. The prevalence of CED among adolescent girls was 60.9%. Significant factors associated with CED included knowledge, nutritional intake (energy, carbohydrates, protein, fat), sleep quality, stress, and family support (p < 0.05), which collectively accounted for 77% of the variance in CED incidence. Conversely, body image showed no significant association. Regarding health impacts, CED was significantly correlated only with self-efficacy (r = -0.270; p < 0.001); hemoglobin levels, menstrual cycles, and academic performance showed no significant associations. Nutrition education programs are needed to improve balanced dietary intake. Furthermore, strengthening the roles of families and schools is recommended to support the prevention and management of CED among adolescent girls.